(untitled) (Scientific journal of the Fergana State University, 2024)
Modern linguistics in general tends to move away from focusing only on the structural aspects of language and moves to a more anthropological approach that studies linguistic phenomena in the context of man, his thinking, spiritual and practical activity. The anthropological approach focuses on the role of humans in creating language and dialogue, which is the main means of communication. This exchange of information is manifested explicitly through texts, with the text itself acting as a tool and result of communication. Thus, this article seeks to analyze the national and cultural aspects of the text and create the basis for effective intercultural communication. These aspects are the manifestation of culture in language and serve as indicators of cultural characteristics. The text preserves and conveys national and cultural meaning, reflecting national identity, traditions, customs, as well as the culture and history of the people. The main way to study intercultural communication through texts is associations, which play a key role in the formation of associative meaning. The results of the study suggest comments related to national culture that reflect the cultural and linguistic context of the text. Highlighting the cultural elements of the center and periphery in the text contributes to the overall understanding and perception of the text.